Magnesium and calcium overaccumulate in the leaves of a schengen3 mutant of Brassica rapa. Issue 3 (8th April 2021) - Alcock, Thomas D; Thomas, Catherine L; Ó Lochlainn, Seosamh; Pongrac, Paula; Wilson, Michael; Moore, Christopher; Reyt, Guilhem; Vogel-Mikuš, Katarina; Kelemen, Mitja; Hayden, Rory; Wilson, Lolita; Stephenson, Pauline; et al.
Abstract: Magnesium (Mg) and calcium (Ca) are essential mineral nutrients poorly supplied in many human food systems. In grazing livestock, Mg and Ca deficiencies are costly welfare issues. Here, we report a Brassica rapa loss-of-function schengen3 ( sgn3 ) mutant, braA.sgn3.a-1, which accumulates twice as much Mg and a third more Ca in its leaves. We mapped braA.sgn3.a to a single recessive locus using a forward ionomic screen of chemically mutagenized lines with subsequent backcrossing and linked-read sequencing of second back-crossed, second filial generation ( BC 2 F 2 ) segregants. Confocal imaging revealed a disrupted root endodermal diffusion barrier, consistent with SGN3 encoding a receptor-like kinase required for normal formation of Casparian strips, as reported in thale cress ( Arabidopsis thaliana ). Analysis of the spatial distribution of elements showed elevated extracellular Mg concentrations in leaves of braA.sgn3.a-1, hypothesized to result from preferential export of excessive Mg from cells to ensure suitable cellular concentrations. This work confirms a conserved role of SGN3 in controlling nutrient homeostasis in B. rapa, and reveals mechanisms by which plants are able to deal with perturbed shoot element concentrations resulting from a "leaky" root endodermal barrier. Characterization of variation in leaf Mg and Ca accumulation across a mutagenized population of B. rapa shows promise for using such populations in breeding programs to increase edible concentrations of essential human and animal nutrients. Abstract : "Leaky" root Casparian strips lead to accumulation of two-fold greater magnesium and ∼35% greater calcium concentrations in leaves of a Brassica rapa mutant.